Prosedur Teknik Penyinaran Metode Intensity Modulated Radiation Therapy(IMRT) Kelenjar Getah Bening Pada Kasus Limfoma Hodgkin (LH) Di Rumah Sakit Umum Pusat DR.Hasan Sadikin - I Made Lana Prasetya; Retno Laksmi Faraningrum; Santo Aloya Dearta Saragih (Pusat riset dan Inovasi Nasional, 2023)
Latar Belakang: Lymph node cancer in the case of Hodkin's Lymphoma is a type of cancer. Lymphoma is a solid tumor of the immune system. Hodgkin lymphoma (HL) accounts for about 10% of all lymphomas. The Intensity Modulated Radiation Therapy (IMRT) technique is one of the cancer treatment techniques in Hodgkin's Lymphoma cases. The aim of this research is to determine the procedure and reasons for using the IMRT technique in lymph node cancer in Hodkin's Lymphoma cases.Metode: This research is qualitative research with a case study approach using retrospective data. The research time is from 24 to 30 May 2023 and the research location is in the Department of Radiation Oncology, RSUP Dr. Hasan Sadikin Bandung. The research subjects consisted of Radiation Oncologists, Medical Physics, Radiotherapists. Researchers collected data from patient medical records, made interview transcripts and carried out data reduction and processed it using open coding, and provided it in the form of quotations and then drew conclusions.Hasil: The procedure for irradiating Hodgkin's Lymphoma using the IMRT technique at the RSHS Department of Radiation Oncology begins with positioning the patient on the examination table with a fixation device and arranging the patient according to the reference point of the CT Simulator and making a thermoplastic mask then carrying out verification and irradiation. The IMRT technique has the advantage of using MLC so that the radiation is modulated according to the contour of the target and the disadvantage of precise dose distribution in limiting the radiation dose to organs at risk.Kesimpulan: In the case of the Department of Radiation Oncology, Dr. Hasan Sadikin Hospital, Bandung, the IMRT technique was used with consideration, namely that the IMRT technique already uses MLC which creates individual blocks automatically according to the projections depicted on the TPS.